Dual system design for a low-ductility concentrically braced frame with a reserve moment frame. (December 2021) - Bradley, Cameron R.; Fahnestock, Larry A.; Hines, Eric M.
Abstract: To address shortcomings of the moderate-seismic design philosophy currently implemented in the United States, this paper proposes design criteria for a Concentrically Braced Dual Frame (CBDF). In contrast to existing low-ductility Concentrically Braced Frame (CBF) systems, such as R = 3 CBF (R3CBF) and Ordinary Concentrically Braced Frame (OCBF) systems, the proposed CBDF design approach explicitly considers the strength and integrity of the post-elastic, degraded (reserve) system. Specifically, the CBDF is defined to consist of a stiff low-ductility primary concentrically braced frame (PCBF) supplemented by a flexible, distributed reserve moment-resisting frame (RMRF). Relative to the R3CBF and OCBF systems, the proposed CBDF system achieves superior collapse performance without the need for costly ductility detailing requirements or substantial changes to traditional seismic design provisions. Consequently, the CBDF system is proposed as a practical, reliable, and cost-effective design alternative to R3CBF and OCBF systems.